2000
DOI: 10.1007/s005860000186
|View full text |Cite
|
Sign up to set email alerts
|

Anterior thoracoscopic spine release in deformity surgery: a meta-analysis and review

Abstract: Videoassisted thoracoscopic surgery (VATS) allows the surgeon to perform an anterior thoracoscopic spine release for spinal deformities. It is an alternative to open thoracotomy. Several years after its introduction the present author gives an update on the indications, surgical techniques, results, and complications of this new technology. A metaanalysis of previously published papers is organized in tables in an attempt to answer all the questions and controversies that this technique has aroused. A series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 16 publications
2
42
0
7
Order By: Relevance
“…With the advent of thoracoscopic techniques for spinal surgery, numerous studies have been published concerning anterior release in AIS [1,2,[11][12][13][18][19][20][21][22][23][24][25][26]. Excision of the intervertebral discs prior to posterior instrumentation is believed to impart additional flexibility and it has been presumed that disc excision improves the correction rate [12,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of thoracoscopic techniques for spinal surgery, numerous studies have been published concerning anterior release in AIS [1,2,[11][12][13][18][19][20][21][22][23][24][25][26]. Excision of the intervertebral discs prior to posterior instrumentation is believed to impart additional flexibility and it has been presumed that disc excision improves the correction rate [12,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal indication for an anterior release in AIS remains unclear: it has been recommended for curves greater than 60° [20], 70° [24], curves greater than 100° [4] and curves greater than 40°i n fulcrum bending [6]. In a meta-analysis it has been shown that in most series using thoracoscopic anterior release, the Cobb angle averaged 65° [2] and even patients with a scoliosis of 42°have been anteriorly released [1]: we are convinced that the additional morbidity by the anterior release is not justified in such cases. Recent paper showed that there is no need for an anterior release even for curves in the 70°-90°range [3] and that in curves up to 100°a single posterior approach with pedicle screw constructs leads to the same coronal correction rate [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [25] recently reported that an open anterior approach may have a deleterious effect on pulmonary function for as long as 5 years postoperatively, after surgical treatment of adolescent idiopathic scoliosis. Video-assisted thoracoscopy (VAT), used for the anterior release, followed by posterior instrumentation for scoliosis treatment [2,29,36,37] can minimize, but not eliminate, the negative effect on pulmonary function, as reported by Newton et al [36].…”
Section: Introductionmentioning
confidence: 97%
“…Recent papers on the need of anterior release in curves between 70°and 100°have shown that the anterior release was unnecessary with the modern segmental instrumentation [3][4][5]. In 2000, we published a meta-analysis of anterior release done with thoracoscopic instrumentation and to our surprise the average Cobb angle of the curves being released was only 65°with a maximum of 80° [6]. Today these thoracoscopic releases are being performed at many centers despite the strong evidence shown as in this paper, that it is unnecessary and of little benefit.…”
mentioning
confidence: 91%